Translation Analysis and Assessment of Poetic Translation: Whitman’s Poetry Translated into Albanian - Pema, Alketa (Richtmann Publishing, 2012)
Among translation issues, poetry translation is the most problematic area challenging both translators and authorities in thefield of translation studies. Translation of poetry as a yet unanalyzed ‘black box’ has been a much debated issue since olden times, withmany pros and cons and dichotomist reasoning as to its possibility or impossibility. This is due to the high cultural prestige of poetrywhich requires time, effort and ingenuity to translate rhythm structures and the figurative language involved. An examination of an actualinstance of Whitman’s poetry translated into Albanian demonstrates that the translation process is guided by case-specific values. Thesevalues, as well as the strategies employed to realize them, are set and agreed by the interested parties during the translation process. Inthe present study, Whitman’s LEAVES OF GRASS and its Albanian translation by S. Luarasi will be focused upon and descriptivelyanalyzed at both linguistic and extra linguistic levels. The aim is to identify the formative elements of versified discourse in the sourceand target texts and to arrive at a tentative model of translation analysis which can serve as a measure fortranslation assessment of poetic genre.